2013
DOI: 10.1103/physrevb.87.161402
|View full text |Cite
|
Sign up to set email alerts
|

Spin symmetry of the bilayer graphene ground state

Abstract: We show nonlinear transport experiments on clean, suspended bilayer graphene that reveal a gap in the density of states. Looking at the evolution of the gap in magnetic fields of different orientation, we find that the groundstate is a spin-ordered phase. Of the three possible gapped groundstates that are predicted by theory for equal charge distribution between the layers, we can therefore exclude the quantum anomalous Hall phase, leaving the layer antiferromagnet and the quantum spin Hall phase as the only p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
57
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(71 citation statements)
references
References 27 publications
14
57
0
Order By: Relevance
“…Bilayer graphene Bilayer graphene has received a lot of attention, mainly because of the enhanced density of states at zero doping due to parabolically touching bands. Such band structures have been shown to be unstable towards spontaneous symmetry breaking [152] and experimental results have revealed signatures of interaction-driven excitonic states in suspended and undoped graphene bilayers [18,19,20,21,22,23,24,25]. Very recently weak-coupling renormalization group calculations have shown that superconductivity emerges upon doping away from these excitonic states [153].…”
Section: Graphene-like Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bilayer graphene Bilayer graphene has received a lot of attention, mainly because of the enhanced density of states at zero doping due to parabolically touching bands. Such band structures have been shown to be unstable towards spontaneous symmetry breaking [152] and experimental results have revealed signatures of interaction-driven excitonic states in suspended and undoped graphene bilayers [18,19,20,21,22,23,24,25]. Very recently weak-coupling renormalization group calculations have shown that superconductivity emerges upon doping away from these excitonic states [153].…”
Section: Graphene-like Systemsmentioning
confidence: 99%
“…[4,5,6,7,8,9,10,11,12,13,14,15,16,17], but most have not been experimentally observed as of yet. One exception is multi-layer graphene systems where there are now experimental reports of an energy gap opening at low temperatures, which has been ascribed to interactions effects [18,19,20,21,22,23,24,25]. Obviously, the possibilities for superconductivity in graphene have also been explored.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8,10] When referring to the geometrical features of "honeycomb lattice" and "height differences for sublattices", silicene is not the only candidate that comes to mind, actually, bilayer graphene (BLG) does also have these features. Recently, several experiments showed clear evidences that BLG at the charge neutrality point had a gapped ground state (the magnitude of the gap is about 2 meV), [18][19][20][21][22][23] where the original degeneracy is considered to be lifted by the formation of certain ordered ground states. Since the nearly quadratic dispersion at low energy leads to finite density of states at the Fermi level, the system is susceptible to even weak interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fascinating potential of exhibiting various ordered phases [2,3] and related quantum critical phenomena [4,5], the Dirac points of monolayer graphene are remarkably stable due to a large quasi-particle Fermi velocity (v F ∼ 10 6 m/s); thus far, ordered phases have only been realized in the presence of (perpendicular) magnetic fields [6]. In this regard, bilayer BLG appears to be propitious, and has already exhibited phenomena strongly suggestive of spontaneous symmetry breaking [7][8][9][10][11], possibly realizing a subset of all the possible ordered states available for the fermion to condense into [12]. But the role of the mesoscopic environment, such as gate configuration, substrate etc., on the nature of the ordered states still lacks a clear understanding [13].…”
mentioning
confidence: 99%
“…Hence, the Zee-man coupling reduces the symmetry of any triplet ordering to O(2), restoring the possibility of KosterlitzThouless transitions at finite temperatures. [45] Recent experiments [10,11] suggest that a layer anti-ferromagnet (LAF) state can be found in BLG. The LAF OP is Ψ † s ( s ⊗ A 4 ) Ψ s .…”
mentioning
confidence: 99%